Initial development of Islamic Envy Management Scale (IEMS) - Sri , Nurul Milla; Ssekamanya, Siraje Abdallah (2015)
Islam discourages the believers from keeping envious feelings in their hearts. In modern psychology, envy is linked with a group of negative mental health outcomes, such as depression, anxiety, and aggressive behaviors. This study is an attempt to develop a scale of envy management based on the teaching of al-Ghazali, one of a Muslim scholar known as Hujjat al-Islam, The Proof of Islam. The Benign and Malicious Envy Scale (BeMaS) developed by Lange & Crusius (2015) was administered to 200 Muslim students of an Islamic higher learning institution in Malaysia to evaluate their benign and malicious tendencies towards envy. Additionally, the Islamic Envy Management Scale (IEMS) was developed in accordance with al-Ghazali‟s proposition on how to eliminate envious feelings among Muslim adults and was administered to the sample. Principal Components Analysis yielded two factors, namely knowledge and action, with a total variance extracted of 55.5%. The resultant scale had a Cronbach Alpha of 0.7. The scale had showed a significant positive correlation with the benign envy and a significant negative correlation with malicious envy.